Impact of technical and physical performance on match outcome over five elite European soccer seasons - Morgans, R.; Orme, P.; Di Michele, R. (The Journal of Sports Medicine and Physical Fitness, 2023)
BACKGROUND: The technical and physical performance, a key part of overall soccer performance, tend to evolve due to changes in game rules, playing styles, and training methodology. Nevertheless, little has been reported in the literature on how match performance has changed over time in elite championships and leagues. Thus, this study aimed to assess the impact of selected technical and physical team performance indicators on match outcome over five seasons in the Russian Premier League. METHODS: Twenty-two technical and physical team performance variables, recorded with an optical tracking system, were examined in 1186 matches played in the Russian Premier League during the 2016-2017 to 2020-2021 seasons. RESULTS: For pooled data in all examined seasons, shots on target were higher in won vs. drawn and lost matches. Percentage of challenges won was higher in won vs. drawn and lost matches. Sprint distance, counterattacks, shots, interceptions, recoveries, crosses, and the percentage of successful tackles all showed small though significant differences between match outcomes. Slightly greater odds of a more favorable match outcome were involved by increases in all selected variables, except crosses, showing an opposite effect. In the 2020-2021 season, ball possession time reported a slightly higher impact on match outcome than in previous seasons. CONCLUSIONS: The present results show that some technical performance variables have a great effect on match outcome, while other technical indicators and physical metrics have a smaller though still potentially relevant impact. These effects do not substantially differ across the five examined seasons.